Pengaruh Product Perceived Quality Dan Citra Toko Terhadap Minat Beli Produk Label Pribadi Indomaret Tanah Grogot - Jumai Latte; Saladin Ghalib; Maryono Maryono (JURNAL BISNIS DAN PEMBANGUNAN, 2015)
The purpose of this research is test of the effect of product perceived quality on store image. Test of the effect of store image on purchase intention. Test of the effect of product perceived quality on purchase intention. Samples in this study are the buyer at Indomaret sample of 115 peoples. Analysis used data is PLS. These results showed that product perceived quality significant effect on store image the effect of 68,65%. Store image significant effect on purchase intention the effect of 27,67%. Product perceived quality not significant effect on purchase intention the effect 16,75%.Keywords: Product perceived quality, store image, purchase intention private label